The snowchild - Gliori, Debi. (London : Myriad Books, 1994)
Katie was lonely because no one would play with her. However, when a beautiful snowfall covers the city, Katie finally makes a friend.
"First published in Great Britain in 1994 by Frances Lincoln Limited"--Page facing t.p.
3.9
K-3.
K-3
Keywords: Friendship -- Fiction; Play -- Fiction; Friendship -- Fiction; Play -- Fiction